2016
DOI: 10.1371/journal.pone.0164693
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Epithelial Attachment on Titanium Surface Coated with Platelet Activating Peptide

Abstract: The aim of this study was to produce epithelial attachment on a typical implant abutment surface of smooth titanium. A challenging complication that hinders the success of dental implants is peri-implantitis. A common cause of peri-implantitis may results from the lack of epithelial sealing at the peri-implant collar. Histologically, epithelial sealing is recognized as the attachment of the basement membrane (BM). BM-attachment is promoted by activated platelet aggregates at surgical wound sites. On the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 30 publications
2
18
0
1
Order By: Relevance
“…As anticipated, platelets rapidly formed aggregates on the PAR4-AP-treated titanium surface that released multiple chemokines and growth factors, yielding an antibacterial epithelial seal with BL attachment. 16 , 17 These studies proved that titanium can be treated to enable strong epithelial attachment. To isolate an advanced peptide with improved epithelial sealing but without undesirable side effects, we conducted a novel panning study on whole-cell platelets.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…As anticipated, platelets rapidly formed aggregates on the PAR4-AP-treated titanium surface that released multiple chemokines and growth factors, yielding an antibacterial epithelial seal with BL attachment. 16 , 17 These studies proved that titanium can be treated to enable strong epithelial attachment. To isolate an advanced peptide with improved epithelial sealing but without undesirable side effects, we conducted a novel panning study on whole-cell platelets.…”
Section: Discussionmentioning
confidence: 90%
“…Sugawara et al 16 reported the establishment of BL-mediated epithelial cell attachment to the treated smooth titanium surface through the use of platelets. The platelets were activated on the smooth titanium surface using protease-activated receptor-4 activating peptide (PAR4-AP) to create an altered surface that promoted epithelial binding.…”
Section: Introductionmentioning
confidence: 99%
“…Perpendicular attachment onto titanium has been reported for laser-machined horizontal microgrooves that limits the direction of cell division to the horizontal plane [13–17]. Other research employed activated platelets on the titanium surface to induce functional epithelial attachment via basal lamina to resist bacterial invasion [18, 19]. A long-lasting vertical level of the epithelial attachment with an ideal biologic seal might be achieved when the above-mentioned technologies are combined with the nanotubes and collagen fibers to modify the implant surface.…”
Section: Introductionmentioning
confidence: 99%
“…Нанесение на имплантаты некоторых белковых протеазных активаторов может способствовать быстрому скоплению тромбоцитов, которые осуществляют выброс большого объема эпителиальных хемоаттрактантов: IGF-I (инсулиноподобный фактор роста), TGF-β (трансформирующий фактор роста) и факторов роста (EGF -эпидермальный фактор роста, VEGF -фактор роста эндотелия сосудов) непосредственно на поверхности титана. In vitro гингивальные эпителиоциты человека на всем протяжении прилегают к поверхности модифицированного таким образом титана с образованием плотных соединений [44].…”
Section: нанесение дополнительного покрытия на имплантируемые материалыunclassified